El papel de Brasil en la conformación y declive del Consejo de Defensa Suramericano (CDS) de UNASUR (2008-2018) - Mamani Torres, Ever Fredy (2025)
At the beginning of this century, South America began to experience a post-hegemonic moment, promoted by various leftist governments; a phenomenon that was favored by both systemic and domestic factors. At the systemic level, following the September 11 attacks, a shift in the United States' stance was observed, as it turned its attention towards the Asian region, resulting in a decrease in its interest in this region. This change allowed Brazilian leadership to take center stage and be accepted by other South American governments. In this context, proposals such as the Union of South American Nations (UNASUR) and, within it, the South American Defense Council (CDS) emerged, driven by Brazil; but, after its formation, it entered a period of decline, leading to its subsequent disappearance. So, we ask ourselves: How did Brazilian ideology and leadership influence the formation and decline of the UNASUR Defense Council during the period 2008 – 2018? To answer this question, we turned to Neoclassical Realism (NR), which allowed us to determine Brazil's role in both the formation and decline of the CDC, considered one of the most dynamic bodies of UNASUR. Empirical evidence has shown that the CDS represented the most productive body of UNASUR, which allowed for the strengthening and transparency of defense cooperation; however, due to Brazilian domestic factors, rather than a change in presidential ideological context, it was sidelined without any other country showing interest in assuming its leadership.